P68 To screen or not to screen for Obstructive Sleep Apnoea (OSA) pre-operatively?. (15th November 2016) - Turnbull, CD; Ball, D; Estevez, ML; Plessis, H Du; Hardinge, M; Nickol, A
Abstract : Background: Anaesthesia worsens OSA, and may lead to respiratory and cardiac complications. Three critical incidents have occurred in the Oxford Hospitals in recent years. OSA is very common at around 5–25%, but half the cases are not diagnosed. So should we screen for OSA pre-operatively? Audit: Over 9 months from July 2015 all patients completed a STOP-BANG questionnaire in a gynaecology pre-operative clinic. Those with snoring and a score of 3 or greater were referred for a sleep study. Data is presented for 102 patients (100 female; 2 transgender) with a mean ± SD age of 55.7 ± 11.4 yrs, BMI 35.8 ± 7.6 kg/m 2 and collar size 40.0 ± 4.8 cm. The rate of non-attendance was high at 19/102 (19%), with those with a lower STOP-BANG score being more likely not to attend. Of those undergoing a sleep study, a new diagnosis was made in 53/83 (52%) patients. Symptoms and OSA/hypoventilation were sufficient for CPAP to be started in 23 patients and NIV in 1 (29% of those screened), with positive diagnoses more likely with higher STOP-BANG scores. The median (IQR) time to CPAP set-up was 80 (52, 100) days, thus a substantial proportion of patients had surgery before treatment. How should we ensure anaesthetic safety for patients at risk of OSA? Completing a sleep study and establishing OSA patients on CPAP prior to surgery would significantly slow the surgical pathway, and there is no evidence that this would improve outcome. However it seems sensible for anaesthesia of all patients deemed at risk of OSA (STOP-BANG 3+) to be managed with special precautions. We pragmatically recommend that all patients found to have a STOP-BANG score of 5+ or strong clinical suspicion of OSA, who are undergoing major surgery AND in whom it is reasonable to delay surgery, are referred for a sleep study prior to surgery. Patients with a STOP-BANG of 3+ not falling into this category should be informed they are at risk of OSA, and advised to seek a referral from their GP to the sleep clinic if they find symptoms of sleepiness troublesome.